Mortality Rate and Predictors Among Women With Obstructed Labor in a Tertiary Academic Medical Center of Ethiopia: A Retrospective Cohort Study - Melaku Desta MSc; Addisu Andualem Ferede MSc (SAGE Publishing, 2023)
Introduction Obstructed labor is one of the most common preventable causes of maternal morbidity and mortality. In Ethiopia, 36% of maternal mortality was due to obstructed labor with uterine rupture. Thus, this study proposed to measure predictors of maternal mortality among women with obstructed labor in a tertiary academic medical center in Southern Ethiopia. Methods An institution-based retrospective cohort study was conducted at Hawassa University Specialized Hospital from July 25 to September 30, 2018. Women who had obstructed labor from 2015 to 2017 were recruited. A pretested checklist was used to retrieve data from the woman's chart. A multivariable logistic regression model was employed to identify variables associated with maternal mortality, and variables with a p -value <.05 were considered significant at 95% CI. Results With a response rate of 96.3%, 156 moms who experienced labor obstruction were included in the study. Obstructed labor caused the deaths of 14 women, resulting in a maternal mortality rate of 8.9% (95% CI: 7.15, 16.4). Maternal mortality from obstructed labor was reduced in women who received antenatal care visits (AOR = 0.25, 95% CI: 0.13, 0.76) and blood transfusions (AOR =  0.49, 95% CI: 0.03, 0.89). Women who experienced uterine rupture (AOR =  6.25, 95% CI: 5.3, 15.6) and antepartum hemorrhage (AOR = 14, 95% CI: 2.45, 70.5) had a greater risk of maternal mortality than women who did not have the corresponding morbidity. Conclusions The center had a higher rate of maternal mortality due to obstructed labor. Early screening and improving the care for women at greatest risk of antenatal and postnatal co-morbidities like uterine rupture and shock were the major priorities and fundamental strategies to decreasing maternal mortality. It also showed that antenatal care visits, early referral, and blood transfusion for women with obstructed labor should be amended in order to lower maternal mortality.